Food combination based on a pre‐hispanic Mexican diet decreases metabolic and cognitive abnormalities and gut microbiota dysbiosis caused by a sucrose‐enriched high‐fat diet in rats. Issue 1 (8th August 2016) - Avila‐Nava, Azalia; Noriega, Lilia G.; Tovar, Armando R.; Granados, Omar; Perez‐Cruz, Claudia; Pedraza‐Chaverri, José; Torres, Nimbe
Abstract : The effect of the consumption of a pre‐Hispanic Mexican diet (PMD) in rats fed a sucrose‐enriched high fat diet is discussed. The presence of soluble and insoluble fiber, antioxidants, polyunsaturated fatty acids and small amounts of docosahexaenoic acid and eicosapentaenoic acid from black beans, corn, tomato, nopal, chia and pumpkin seeds synergistically ameliorate some biochemical abnormalities in brain, adipose tissue and liver produced by obesity. Abstract : Scope: There is few information about the possible health effects of a food combination based on a pre‐hispanic Mexican diet (PMD). This diet rich in fiber, polyphenols, a healthy ratio of omega 6/omega 3 fatty acids, and vegetable protein could improve carbohydrate and lipid metabolism, gut microbiota and cognitive function. Methods and results: We examined the effect of a PMD in a sucrose enriched high‐fat model. The PMD contains corn, beans, tomato, nopal, chia and pumpkin seeds in dehydrated form. Following induction of obesity, rats were fed PMD. PMD consumption decreased glucose intolerance, body weight gain, serum and liver triglycerides and leptin. In addition, PMD decreased the size of the adipocytes, and increased the protein abundance of UCP‐1, PPAR‐α, PGC1‐α and Tbx‐1 in white adipose tissue. Finally, the PMD significant decreased hepatic levels of ROS, oxidized proteins and GSSG/GSH ratio and an increase in the relative abundance of Bifidobacteria and the improvement of cognitive function. Conclusion: Consumption of a PMD decreased the glucose intolerance and the biochemical abnormalities caused by the obesity by increasing the abundance of proteins involved in fatty acid oxidation, decreasing the oxidative stress and modifying the gut microbiota.